Hypertension control and care at Mulago Hospital ambulatory clinic, Kampala-Uganda. (December 2016) - Ssinabulya, Isaac; Nabunnya, Yvonne; Kiggundu, Brian; Musoke, Charles; Mungoma, Michael; Kayima, James
Abstract Background Hypertension is as prevalent in many developing countries, as in the developed world and is the leading cause of cardiovascular morbidity and mortality in Africa. The control of hypertension in this resource limited setting is inadequate, a situation that translates into poorer outcomes in form of increasing incidences of stroke, heart failure, kidney failure and therefore early cardiovascular death. Methods This was a chart review of all the patients seen during the months of September 2012 to February 2013. We determined the level of blood pressure control, basic investigations documented as well as the choice of hypertensive treatment among patients attending a hypertension clinic in a national referral hospital, Mulago. Results Of the 741 patients whose charts were reviewed the median age was 60 years, Inter quartile range (IQR) was 51–71. Six hundred forty-two (86.6%) were females. Blood pressure (BP) control defined as BP lowering to at least 140/90 was seen in only 198 (26.7%) patients. Biophysical measurement documentation was very low especially for waist and hip circumference at 0.3%. Majority of patients, 476 (64.2%) had at least one documented investigation for the complications of hypertension. Only 103 (13.9%) had all investigations documented in their charts. The investigations included; complete blood count (CBC), urinalysis, renal function tests (RFTs), Chest X-Ray (CXR), echocardiography (Echo) and electrocardiography (ECG). The commonly documented investigations were RFTs (45.5%), ECG (45.2%) and Echo (44.2%). The commonly prescribed anti hypertensive medications were; Angiotensin receptor blockers (ARBs)/Angiotensin converting enzyme inhibitors (ACEI) (72.74%), calcium channel blockers (72.3%) and thiazide diuretics (68.6%). Majority of patients were receiving three anti hypertensive medications 313 (42.2%), with 149 (43.6%) of these, on an ACEI/ARB, a calcium channel blocker and a thiazide diuretic. Conclusion Blood pressure control is suboptimal in a tertiary clinic setting at Mulago hospital and documentation of investigations is inadequate. ARB/ACEI, Calcium channel blockers and thiazide diuretics were the commonly prescribed anti hypertensive medications. There is a great need to investigate for renal and cardiac complications as well as exploring reasons for inadequate blood pressure control and consider appropriate interventions to avert bad outcomes.